PENTINGNYA METODE MONTESSORI DALAM MENGEMBANGKAN POTENSI DIRI PESERTA DIDIK DI SD TIGA BAHASA RUKUN HARAPAN JEMBER - Nifa Triyanti Kiuk; Yusak Noven Susanto S.Th, M.Pd (Sekolah Tinggi Teologi Duta Panisal, 2023)
The Montessori method in the learning process, which is based on the principle of the Montessori method that a child's education appears to coincide with the stages of the potential development of learners. The characteristic of the Montesssori method is to emphasize the activities that are raised by the children themselves which can stimulate students to learn actively in learning and can develop students' potential. In this study, researchers used qualitative methods using a case study approach, while the data collection techniques used were observation, interviews and documentation. In collecting data, researchers used the Spradly data analysis model. Data analysis was carried out. It was concluded that the Montessori method is also a method that can develop the potential of students, so it is necessary to introduce the Montessori method in more depth to educators at SD Tiga Bahasa Rukun Harapan, namely by application of understanding to educators regarding the Montessori method.